Síndrome de Prader-Willi, bajo el enfoque de la rehabilitación. Reporte de caso - Tatiana Martínez Lozano; Jessica Henríquez; Ascela Vásquez; Raxa Aguilar (Revista Médica Hondureña)
Introduction: Prader-Willi syndrome (PWS) is a complex genetic disorder of neurodevelopment, its incidence is estimated around 1:25,000 live births. In Honduras the prevalence and incidence of PWS is unknown, however, there is information of two previously reported cases in the years of 2008 and 2014, captured in different municipalities of the country. It is caused by the loss of genetic expression of paternal chromosome 15q11-q13. It presents clinical manifestations such as muscular hypotonia, characteristic facial features, cognitive deficits, behavioral alterations, hyperphagia and obesity. In spite of being a rare entity, the importance of submitting people who have it to a comprehensive rehabilitation program is described; in Honduras we do not have reports of evolution of previous cases. Case description: We present the case of a female infant who was referred to the Centro de Rehabilitación Integral Teletón at the age of 7 months because she presented poor mobility, poor sucking and generalized muscular hypotonia since birth, in addition to global psychomotor developmental delay; she was diagnosed as PWS at the age of 12 months. She underwent a comprehensive rehabilitation program in the areas of early stimulation, neurorehabilitation, multisensory stimulation, among others, obtaining clinical improvement in all developmental spheres evaluated. Conclusion: Timely management and diagnosis, as well as the early implementation of rehabilitation plans allow this population to improve their medical conditions, obtain and improve their developmental milestones, achieving greater functionality and quality of life in the short, medium and long term.